Respiratory Health Inequities Experienced by Low-Income Children and Parents. Issue 3 (2nd July 2016) - Stewart, Miriam; Masuda, Jeffrey; Evans, Joshua; Letourneau, Nicole; Edey, Jocelyn
ABSTRACT: As some respiratory conditions are more prevalent among children who are low income, the aim of this study was to describe challenges experienced by children and parents coping with poverty and respiratory health problems and relevant service inequities. Children and parents who are low income (n = 69) were interviewed to identify challenges connected with poverty, compounded by chronic respiratory conditions. Poverty exacerbated challenges linked to respiratory conditions, and respiratory illness increased problems experienced by people living in poverty. Participants reported multiple factors that contributed to poverty and contended that service providers didn't understand challenges associated with poverty and pulmonary problems. Interviewed service providers (n = 29) reinforced challenge complexities.